EDITORIAL: ARTIFICIAL INTELLIGENCE AND ITS TRANSFORMATIVE IMPACT ON SCIENTIFIC PUBLISHING - Abubakar Munir (International Journal of Pharmacy & Integrated Health Sciences, 2025)
Artificial Intelligence (AI) has revolutionized several industries, and scientific publishing is no exception. From peer review automation to the detection of plagiarism and manuscript proofing, AI is revolutionizing research production, dissemination, and evaluation. Although AI brings tremendous potential to automate publishing, it raises significant questions regarding ethics and integrity that must be addressed correctly (1).